REENGINEERING THE CITY OF JAKARTA TO BECOME A RESILIENT AND SUSTAINABLE GLOBAL CITY BASED ON THE EFFECTIVENESS OF STATE PROPERTY MANAGEMENT EX-MINISTRIES/CENTRAL LEVEL INSTITUTIONS - K.P.Suharyono S.Hadiningrat; Teguh Yuwono (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The city of Jakarta after the State Capital must be re-engineered in such a way that it becomes a resilient and sustainable global city for the progress of the nation and the Unitary State of the Republic of Indonesia. This has been initiated with the passage of Law No. 2 of 2024 concerning the Jakarta Special Region (DKJ) and the Jakarta City Regional Spatial Plan for 2024-2024. It needs the commitment of the central government and the DKJ government so that the implementation is faster and more permanent by strengthening the collaboration of the penta helix involving elements of the government, academia, industry, society and the media. This study uses a qualitative descriptive method to find and describe the variables in a narrative (non-numeric) about the city of Jakarta becoming a resilient global city and a sustainable city so that it has global competitiveness in prospering its community without neglecting environmental sustainability. From the discussion, it was concluded that the city of Jakarta, after not becoming the capital of the country, must be re-engineered into a global city that is resilient and sustainable following international standards so as to provide more benefits and have global competitiveness that is professionally managed. And institutional support, human resources, technology and financing are needed; including from its use as Ex-Ministry/Central Government Institution State Property in Jakarta. From these conclusions, it is recommended to the DKJ Government to implement the Regional Spatial Planning consistently with support from the Central Government, including financing that can be prepared from the partial utilization of State Property (BMN) ex-Ministries/Central Government Institutions which were abandoned due to moving to the Nusantara Capital City.